Enhancing Maternal Baby Massage Behavior in Makassar City through AH Baby Massage-Based Training - Ayatullah Harun; Fatmawati Amir (Babali Nursing Research, 2023)
Introduction: Current baby massage interventions have been shown to be effective in boosting baby growth so it is important to socialize baby massage to improve parents behavior so that they can do baby massage independently. The aim of this study was to evaluate the effectiveness of baby massage training based on the AH Baby Massage application to enhance mother's intentions, mother knowledge, mother attitude and mother skills doing baby massage. Methods: This research uses quantitative methods with the design of one group pretest – posttest. To a mother who has a baby of 35 mothers in the area of work practice Bidan Independent District Biringkanaya City of Makassar. Results: The results of the study were obtained, there were differences in the mother's intentions, the mother’s knowledge of her attitude and her skills in performing baby massages before and after the intervention of baby massage training based on the AH Baby Massage application with (p value < 0.05). Conclusion: The conclusion of the baby massage training based on the AH Baby Massage app has been shown to improve the mother's intentions, knowledge, attitude and skills of the mother doing baby massage so it requires the role of Puskesmas, health care and kader involvement in socializing baby massage.